Eco-Onenessism: An Environmental Ethics of Interconnectedness for Addressing Climate Change - Osebor, Ikechukwu Monday (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Climate change represents one of the most pressing global challenges of the 21st century. The rising of global temperatures, extreme weather events, melting ice caps, and shifting ecosystems are impacts of climate change. The moral implications of climate change have far-reaching effects on biodiversity, global stability, and ecological well-being. Using the philosophical method of analysis, the study finds that the cause of climate change is the human inability to see Earth as one and the lack of oneness; the ecological trinity in the hierarchy of being. The objective of the study is to recommend eco-onenessism by policymakers through teaching and learning in schools to affirm the unity of existence in the state of being. This philosophy stresses the interconnectedness of nature. Although the study finds that the implementation of Eco-onenessism is challenged by human anthropocentrism, yet it offers humanity a comprehensive framework that aligns environmental preservation with a sustainable future.